A Novel Intravesical Dextrose Injection Improves Lower Urinary Tract Symptoms on Interstitial Cystitis/Bladder Pain Syndrome - Chen, Chin-Li; Kao, Chien-Chang; Yang, Ming-Hsin; Fan, Gang-Yi; Cherng, Juin-Hong; Tsao, Chih-Wei; Wu, Sheng-Tang; Cha, Tai-Lung; Meng, En (Frontiers in Pharmacology, 2021)
Interstitial cystitis/bladder pain syndrome (IC/BPS) is a painful recurrent condition characterized by the discomfort of the bladder, and current treatment options have limited effectiveness. Prolotherapy is a well-known regenerative treatment that induces local inflammation and immune system promoting tissue repair. In this study, we investigated the effects of dextrose prolotherapy in a rat model of IC/BPS and patients with IC/BPS. We used cyclophosphamide (CYP) to induce IC/BPS in rats. We found that dextrose prolotherapy in CYP rats could improve the instability of the bladder, reduce frequent urination, and increase the regeneration of the glycosaminoglycan layer of the bladder epithelium. We also enrolled 29 patients with IC/BPS who received intravesical injections of 10% dextrose with a maximum of five planned therapy cycles for up to 12 weeks. Patient characteristics and a 3-day voiding diary before treatment were recorded. Patient responses were examined using IC/BPS-related questionnaires. Furthermore, expressions of growth factors and cytokines were analyzed. The results demonstrated that dextrose prolotherapy in patients with IC/BPS reduced the frequency of treatment through time and significantly reduced the incidence of nocturia and questionnaire scores associated with symptoms. The alteration of growth factors and cytokines exhibited safe treatment and a remarkable stimulation of tissue remodeling. In summary, our study demonstrated that dextrose prolotherapy is a potential treatment strategy for IC/BPS disease management.